The impact of marketing mix elements towards customer buying decision in purchasing Celcom broadband: case study in Bandar Melaka / Mohammad Ikhwan Marti - Marti, Mohammad Ikhwan (Faculty of Business and Management, 2008)
As a company that has being appointed to promote and sell the Celcom Broadband by Celcom (M) Berhad, One Two Three Communications (M) Sdn Bhd has to maintain its sales performance every month. Based on their monthly sales report, the company faced a problem not achieving the monthly sales target. The research of “The Impact of Marketing Mix Elements towards Customer Buying Decision in Purchasing Celcom Broadband:Case Study in Bandar Melaka” has several objectives which is first, to determine whether the marketing mix elements give an impact towards customer buying decision in purchasing Celcom Broadband. Secondly, to identify the most influencing marketing mix elements towards customer buying decision in purchasing Celcom Broadband. And lastly, to provide suggestion and recommendation that can help One Two Three Communication to enhance their sales on Celcom Broadband.